Homer's Odyssey : a reading guide - Power, Henry (Lecturer in English) (Edinburgh : Edinburgh University Press, 2011)
A fresh and exciting approach to this great work of classical literatureHenry Power provides an overview of the whole poem with detailed commentary of the crucial moments. Readers are encouraged to consider both the oral origins and the rich literary reception of this early epic whilst responding to core themes within it.Key Features'Teaching the Text' section with fresh ideas and flexible teaching templates that can be adapted to existing course structuresIncludes extensive extracts from the poem accompanied by a headnote, commentary and glossesIncludes an annotated bibliography.
Frontmatter -- Contents -- Acknowledgements -- Note on the text -- Series Preface -- 1. Mapping and Making -- 2. Four Ways of Approaching the Poem -- 3. Selections from the Odyssey -- 14. Contexts for Reading -- 5. Teaching the Text -- 6. Suggested Further Reading -- References -- Index
JSTOR
Keywords: Homer; Odyssey (Homer); Epic poetry, Greek -- History and criticism; Poésie épique grecque -- Histoire et critique; Literary Criticism -- Poetry; POETRY -- Ancient & Classical; LITERARY CRITICISM / Poetry; Epic poetry, Greek; Criticism, interpretation, etc